A novel universal gripper based on meshed pin array. (13th March 2019) - Mo, An; Zhang, Wenzeng
Conventional grippers are designed for specific applications. They often encounter difficulties when grasping different objects in unstructured environments. This article introduces a novel gripper to challenge the universal grasp capability. Passively slidable pins are array arranged in the gripper. By meshing of pin's elliptical contour, shape adaption to various objects is achieved in both vertical and horizontal directions using a single motor. Contact force is analyzed based on static and kinetic friction. Kinematic simulation on the grasping process reveals the interaction between critical parameters and the overall grasp performance. To conclude, a prototype pin array gripper demonstrates high adaptability to various objects in real-world testing.